Biodegradable 3D printing material and preparation method thereof
By using degradable resins and modified plant fiber powders in 3D printing materials, combined with additives such as nanofillers, the problem of insufficient mechanical properties of existing materials is solved, and the material properties with high toughness, high heat resistance and strength are achieved, and its application range is expanded.
Patent Information
- Application Number
- CN202510136193.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-18
AI Technical Summary
Existing 3D printing materials have shortcomings in mechanical properties, heat resistance and toughness, which limits their application in the field of 3D printing.
Degradable resin and modified plant fiber powder are used as the main components, and the porous structure and strengthening interface are formed by adding nanofillers, chain extenders, dispersants and additives to improve the mechanical properties of the material.
It realizes the high toughness, high temperature resistance, high strength and good mechanical properties of 3D printing materials, expanding its application range in the field of 3D printing.
Smart Images

Figure BDA0005263299610000061 
Figure BDA0005263299610000081
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of 3D printing materials, and more specifically, the present invention relates to a biodegradable 3D printing material and a preparation method thereof. Background Art
[0002] 3D printing technology, also known as rapid prototyping technology and additive manufacturing technology, was born in the late 1980s. It is a high-tech manufacturing technology based on material accumulation. It is based on digital model files, uses powdered metal or plastic and other bondable materials, and constructs objects by printing layer by layer. It integrates mechanical engineering, computer-aided design (CAD), reverse engineering technology, layered manufacturing technology, numerical control technology, material science, and laser technology. It is called "manufacturing technology with industrial revolutionary significance."
[0003] Fused deposition modeling (FDM) technology is also known as fused deposition manufacturing, fused deposition modeling, etc. FDM equipment is easy to maintain, has a wide range of molding materials, a high degree of automation, and occupies a small area. It is currently widely used in the preparation of aerospace models and accessories, automotive fields, medical devices and models.
[0004] Currently, the most common 3D printing materials on the market are acrylonitrile butadiene styrene (ABS) and polylactic acid (PLA). ABS has good mechanical properties and high toughness, and is widely used in industrial 3D printing, but it produces unpleasant gases during printing, is not suitable for offices and other environments, and is opaque; PLA has no unpleasant odor when melted during printing and is degradable, but has poor heat resistance and mechanical properties, and is especially prone to brittle fracture, which greatly limits the use of printed objects.
[0005] Fixing CO2 into biodegradable materials can simultaneously alleviate the three problems of global warming, oil resource depletion and "white pollution". Polypropylene carbonate (polymethyl ethylene carbonate, PPC), a representative of carbon dioxide-based polymers, is prepared by polymerization of CO2 and propylene oxide (PO) as monomers. It is a completely biodegradable material with good barrier properties and high permeability. However, conventional binary polymerized PPC has poor thermal properties, especially low thermal decomposition temperature and glass transition temperature. At present, physical or chemical modifications are generally required to improve the performance of PPC. PPC can be copolymerized and modified with monomers such as phthalic anhydride or cyclohexane oxide to form a ternary copolymer or a quaternary copolymer. The glass transition temperature and thermal stability of PPC can be significantly improved, but the mechanical properties of the material, especially the toughness, are still relatively low, thus limiting its application.
[0006] At present, in order to improve the mechanical properties of biodegradable materials and expand the scope of application, inorganic non-metallic mineral fillers such as talcum powder and diatomaceous earth are often added to improve the mechanical properties of the products. Generally speaking, the smaller the particle size of the inorganic non-metallic mineral filler, the better the mechanical properties of the composite material when it is evenly dispersed. However, while reducing the particle size of the filler particles, the processing technology becomes complicated and the cost increases accordingly. In addition, the inorganic non-metallic mineral filler has poor biodegradability and poor compatibility with polymers. When compounded, it is easy to form voids, agglomerates and defects on the interface of the composite material, reducing the interface strength. Therefore, the addition of inorganic non-metallic mineral fillers will not only reduce the biodegradability of the composite material, but also reduce the compatibility of the composite material, and the cost is high. It greatly limits its scope of application, especially in the field of 3D printing. The development of biodegradable 3D printing materials must overcome the above problems. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a biodegradable 3D printing material that meets the requirements of 3D printing materials and has a woody feel and has the advantages of biodegradability, high toughness, high temperature resistance, high strength and easy processing.
[0008] Another object of the present invention is to provide a method for preparing a biodegradable 3D printing material.
[0009] In one aspect, the present invention provides a biodegradable 3D printing material, characterized in that it comprises, by weight:
[0010] 70-80 parts of degradable resin, 15-30 parts of modified plant fiber powder, 0.1-0.5 parts of chain extender, 0.5-2 parts of nano filler, 0.1-0.5 parts of dispersant and 0-7.5 parts of auxiliary agent;
[0011] Wherein, the particles of the modified plant fiber powder have a porous structure; the nanofiller is combined in the internal pores and the outer surface of the modified plant fiber powder.
[0012] In some embodiments, the degradable resin may refer to a carbon dioxide-based copolymer, examples of which include, but are not limited to, propylene oxide / carbon dioxide / phthalic anhydride terpolymer, propylene oxide / carbon dioxide / phthalic anhydride / cyclohexane oxide tetrapolymer, or a combination thereof.
[0013] In some embodiments, the modified plant fiber powder may refer to wood fiber powder, bamboo fiber powder, hemp fiber powder, fruit shell powder, crop shell powder, etc., which are modified to make their particles have a porous structure, and are preferably selected from one or more of modified bamboo powder (e.g., moso bamboo, nan bamboo, hemp bamboo), modified coconut shell powder, and modified rice husk powder. In some embodiments, the particle size of the modified plant fiber powder is 50 to 300 mesh. In some embodiments, the pore size of the particles of the modified plant fiber powder is 5nm to 20μm; preferably, the specific surface area of the particles of the modified plant fiber powder is 300m 2 / g~600m 2 / g, more preferably 400m 2 / g~600m 2 / g. In some embodiments, the surface of the particles of the modified plant fiber powder has active functional groups, which form intermolecular hydrogen bonds and / or van der Waals forces with the nanofiller. The active functional groups can be oxygen-containing functional groups, such as hydroxyl groups. Through alkali treatment, part of the impurities such as amorphous pectin, lignin, hemicellulose, etc. in the fiber are removed, and the hydrogen bonds are destroyed, and finally the oxygen-containing functional groups such as hydroxyl groups are grafted on the powder surface. In some embodiments, the modified plant fiber powder can be obtained by placing the plant fiber powder and the dispersant powder in an alkaline solution (for example, sodium hydroxide or potassium hydroxide aqueous solution) for mixing, washing and drying.
[0014] In some embodiments, the chain extender may be one or more selected from a multifunctional epoxy oligomer chain extender, an epoxy polymer chain extender, and an amine chain extender. In some embodiments, the multifunctional epoxy oligomer chain extender includes one or more selected from ADR-4368 chain extender, ADR-4400 chain extender, and ADR-4370 chain extender, the epoxy polymer chain extender includes one or more selected from SAG-008 chain extender, 6059 chain extender, and 100G chain extender, and the amine chain extender includes one or more selected from ethylenediamine, diethylenetriamine, triethylenetetramine, and 3-methylaminopropylamine.
[0015] In some embodiments, the nanofiller may refer to carbon nanofillers, metal oxide nanofillers, ceramic nanofillers, polymer nanofillers, etc., examples of which include, but are not limited to, one or more selected from hydroxyapatite and calcium carbonate. In some embodiments, the average particle size of the hydroxyapatite is 50 to 100 nm; the average particle size of the calcium carbonate is 200 to 500 nm.
[0016] In some embodiments, the dispersant may include one or more selected from ethylenediaminetetraacetic acid, sodium bisulfite, and disodium ethylenediaminetetraacetate.
[0017] In some embodiments, the auxiliary agent may refer to one or more selected from plasticizers and antioxidants. In some embodiments, the plasticizer includes one or more selected from epoxidized soybean oil and tributyl citrate. In some embodiments, the antioxidant includes one or more selected from antioxidant 1010, antioxidant 1098, and antioxidant 168. In some embodiments, the amount of the plasticizer may be 1 to 5 parts, and / or the amount of the antioxidant may be 0.5 to 5 parts, preferably, the amount of the antioxidant is 1 to 2 parts.
[0018] According to the present invention, unless otherwise specified, the parts of the raw materials or components used are parts by weight.
[0019] In another aspect, the present invention provides a method for preparing the above-mentioned biodegradable 3D printing material, comprising the following steps:
[0020] S1, preparing modified plant fiber powder: placing plant fiber powder and a dispersant in an alkaline solution (for example, sodium hydroxide or potassium hydroxide aqueous solution) for mixing, washing and drying to obtain modified plant fiber powder;
[0021] S2, dispersing the modified plant fiber powder obtained in S1 in water, adding nanofillers for mixing, so that the nanofillers are combined in the internal pores and the outer surface of the modified plant fiber powder, and drying to obtain a mixed product;
[0022] S3, putting the mixed product obtained in S2, the biodegradable resin, the chain extender, and the additive into a mixer, and stirring for, for example, 3-5 minutes to obtain a mixture;
[0023] S4, adding the mixture obtained in S3 into an extruder, and obtaining a biodegradable 3D printing material through melt blending, extrusion, water cooling, air drying, and pulling. In particular, the extruder is a twin-screw extruder, wherein the temperature zones 1 to 6 of the twin-screw extruder are set to 80-110°C, 145-175°C, 160-190°C, 160-190°C, 150-180°C, and 145-175°C, respectively; and the main engine speed is 2-30rpm.
[0024] In some embodiments, in step S1, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution with a mass fraction of 1%.
[0025] In some embodiments, in step S1, the treated plant fiber powder is washed with distilled water until it is neutral.
[0026] The biodegradable 3D printing material provided in this application has at least the following beneficial effects:
[0027] (1) The modified plant fiber powder is used. Compared with the existing technology, less solvent is used in the modification process. It not only has the advantages of simple process, low cost, renewability, and green environmental protection, but also the particles of the modified plant fiber powder have a porous structure, which increases the specific surface area and surface roughness.
[0028] At the same time, the nanofiller is combined with the internal pores and the outer surface of the modified plant fiber powder, which not only improves the intermolecular binding force between the nanofiller and the modified plant fiber powder, and improves the compatibility; it also further improves the surface roughness of the modified plant fiber powder, and enhances the interfacial adhesion between it and components such as degradable resins. Compared with the existing technology, it has a better modification effect, improves the strength, toughness and other mechanical properties of carbon dioxide-based polymer biodegradable 3D printing materials, and expands its application range.
[0029] (2) The added chain extender can form hinges between the modified plant fiber powder and the matrix such as the degradable resin through in-situ interfacial reaction, thereby improving the comprehensive properties of the biodegradable 3D printing material such as the relative molecular weight and mechanical properties. The addition of a dispersant can increase the dispersibility of the plant fiber powder, and the additive can further improve the dispersibility of each component in the composite material and increase the plasticity of the polymer.
[0030] The material of the present invention ensures certain heat resistance, strength and toughness, and has good mechanical properties, so that the printed parts can have good durability and impact resistance during use. In short, the present invention is a low-cost, high-performance degradable 3D printing material. DETAILED DESCRIPTION
[0031] Hereinafter, the present invention will be described in detail by way of examples. However, the examples provided herein are only for illustrative purposes and are not intended to limit the present invention.
[0032] Example
[0033] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0034] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0035] Bamboo powder was purchased from Shijiazhuang Wangjing Mineral Products Company, bamboo powder specification: 100 mesh.
[0036] Hydroxyapatite was purchased from Hebei Qiansheng Biotechnology Co., Ltd., and the particle size of hydroxyapatite was 80 nm.
[0037] ADR-4368 was purchased from BASF.
[0038] Epoxidized soybean oil was purchased from Shandong Jiexinao Chemical Company.
[0039] 1098 was purchased from BASF.
[0040] 1010 was purchased from BASF.
[0041] Sodium bisulfite was purchased from Qingdao Jielong Chemical Company.
[0042] The preparation process of propylene oxide / carbon dioxide / phthalic anhydride copolymer as a carbon dioxide-based terpolymer is as follows:
[0043] Under anhydrous and oxygen-free conditions, 4 mol of propylene oxide, 1 mol of phthalic anhydride, and 10 mmol of triethyl boron catalyst were added to a 500 ml stainless steel reactor, and 1 MPa of carbon dioxide was introduced. After reacting at a reaction temperature of 70°C for 8 hours, the temperature was lowered to 25°C, and unreacted carbon dioxide was slowly released. An appropriate amount of acetic acid aqueous solution was dropped to quench and terminate the reaction, and the polymer was precipitated from ethanol. Then, the washed product was placed in a vacuum oven for drying to obtain a propylene oxide / carbon dioxide / phthalic anhydride terpolymer.
[0044] The preparation process of propylene oxide / carbon dioxide / phthalic anhydride / cyclohexene oxide copolymer as a carbon dioxide-based tetrapolymer is as follows:
[0045] Under anhydrous and oxygen-free conditions, 4 mol of propylene oxide, 1 mol of phthalic anhydride, 100 mmol of cyclohexene oxide, and 10 mmol of triethyl boron catalyst were added to a 500 ml stainless steel reactor, and 1.1 MPa of carbon dioxide was introduced. After reacting at a reaction temperature of 70°C for 8 hours, the temperature was lowered to 25°C, and unreacted carbon dioxide was slowly released. An appropriate amount of acetic acid aqueous solution was dropped to quench and terminate the reaction, and the polymer was precipitated from ethanol. Then, the washed product was placed in a vacuum oven for drying to obtain a propylene oxide / carbon dioxide / phthalic anhydride / cyclohexene oxide tetrapolymer.
[0046] The formulas of the embodiments of the present invention and the comparative examples are shown in Table 1 below.
[0047] Table 1
[0048]
[0049] Example 1
[0050] (1) According to the formula of Example 1# listed in Table 1, bamboo powder and sodium bisulfite were placed in a sodium hydroxide aqueous solution with a mass fraction of 1% and stirred for 3-5 hours, and then repeatedly rinsed with distilled water until neutral and placed in a drying oven at 100°C for 12 hours to remove moisture and residual dispersant, thereby obtaining a modified bamboo powder with a porous structure. The modified bamboo powder was measured by gas adsorption method, and the pore size was 10-20 μm, and the specific surface area was 400 m 2 / g~600m 2 / g.
[0051] (2) dispersing the modified plant fiber powder obtained in step (1) in water, adding nanofiller hydroxyapatite for mixing, so that the nanofiller hydroxyapatite is combined with the internal pores and the outer surface of the modified bamboo powder, and drying to obtain a mixed product;
[0052] (3) placing the mixed product obtained in step (2) with the biodegradable resin, ADR-4368, epoxidized soybean oil, 1098, and 1010 into a mixer and stirring for 3-5 minutes to obtain a mixture;
[0053] (4) The mixture obtained in step (3) is added into the hopper of a twin-screw extruder, and is melt-blended and extruded. The temperature of the twin-screw extruder is set to 95° C., 160° C., 180° C., 180° C., 170° C., and 160° C. in zones 1 to 6, respectively, and the main engine speed is 15 rpm. The mixture is then cooled in a water tank, air-dried with a hair dryer, and pulled to obtain the biodegradable 3D printing material.
[0054] Example 2
[0055] The biodegradable 3D printing material was prepared in the same manner as in Example 1 except that the dosage of Example 2# was used according to Table 1.
[0056] Comparative Example 1
[0057] (1) According to the formula of comparative example 1# in Table 1, the biodegradable resin, ADR-4368, epoxy soybean oil, 1098 and 1010 were placed in a mixer and stirred for 3-5 minutes to obtain a mixture;
[0058] (2) The mixture obtained in step (1) is added into the hopper of a twin-screw extruder, and is melt-blended and extruded. The temperatures of the twin-screw extruder are set in zones 1 to 6 to 95° C., 160° C., 180° C., 180° C., 170° C., and 160° C., respectively, and the main engine speed is 15 rpm. The mixture is then cooled in a water tank, air-dried with a hair dryer, and pulled to obtain a biodegradable 3D printing material.
[0059] Comparative Example 2
[0060] (1) According to the formula of comparative example 2# in Table 1, the biodegradable resin, epoxy soybean oil, 1098 and 1010 were placed in a mixer and stirred for 3-5 minutes to obtain a mixture;
[0061] (2) The mixture obtained in step (1) is added into the hopper of a twin-screw extruder, and is melt-blended and extruded. The temperatures of the twin-screw extruder are set in zones 1 to 6 to 95° C., 160° C., 180° C., 180° C., 170° C., and 160° C., respectively, and the main engine speed is 15 rpm. The mixture is then cooled in a water tank, air-dried with a hair dryer, and pulled to obtain a biodegradable 3D printing material.
[0062] Test Case
[0063] (1) Tensile strength: The tensile strength was tested according to GB / T1040-2006, with a tensile rate of 50 mm / min.
[0064] (2) Notched impact strength: Notched impact strength is tested according to GB / T 1043-1993.
[0065] (3) Tg: Differential scanning calorimetry, nitrogen atmosphere, from room temperature to 10°C min -1 The temperature was raised to 200°C at a rate of 10°C min-1 and then kept constant for 5 min. -1 The temperature was cooled to 30℃ at a cooling rate of 10℃·min. The temperature was kept constant for 5min to eliminate the thermal history. -1 The temperature was raised to 200°C at a heating rate of , and the curve was recorded to calculate Tg.
[0066] The product performance parameters of the embodiments and comparative examples are shown in Table 2 below.
[0067] Table 2
[0068]
[0069] It can be seen that the biodegradable 3D printing material prepared by the present invention has higher mechanical properties, toughness and thermal properties than the unmodified material, which expands the application range of the biodegradable 3D printing material.
Claims
1. A biodegradable 3D printing material, characterized in that: In parts by weight: 70-80 parts of degradable resin, 15-30 parts of modified plant fiber powder, 0.1-0.5 parts of chain extender, 0.5-2 parts of nano filler, 0.1-0.5 parts of dispersant and 0-7.5 parts of auxiliary agent; Wherein, the particles of the modified plant fiber powder have a porous structure; the nanofiller is combined in the internal pores and the outer surface of the modified plant fiber powder.
2. The biodegradable 3D printing material according to claim 1, characterized in that: The degradable resin is a carbon dioxide-based copolymer, preferably one or more selected from propylene oxide / carbon dioxide / phthalic anhydride terpolymer and propylene oxide / carbon dioxide / phthalic anhydride / cyclohexane oxide tetrapolymer.
3. The biodegradable 3D printing material according to claim 1 or 2, characterized in that: The modified plant fiber powder is selected from one or more of wood fiber powder, bamboo fiber powder, hemp fiber powder, fruit shell powder, and crop shell powder, which are modified to have porous structures, and is preferably selected from one or more of modified bamboo powder, modified coconut shell powder, and modified rice husk powder. Preferably, the particle size of the modified plant fiber powder is 50 to 300 meshes, and more preferably, the pore size of the modified plant fiber powder is 5 nm to 20 μm. More preferably, the specific surface area of the modified plant fiber powder is 300 m 2 / g~600m 2 / g, more preferably 400m 2 / g~600m 2 / g, further preferably, the surface of the particles of the modified plant fiber powder has active functional groups, forming intermolecular hydrogen bonds and / or van der Waals forces with the nanofiller, and further preferably, the modified plant fiber powder is obtained by mixing the plant fiber powder and the dispersant powder in an alkaline solution, washing and drying.
4. The biodegradable 3D printing material according to any one of claims 1 to 3, characterized in that: The chain extender is one or more selected from multifunctional epoxy oligomer chain extenders, epoxy polymer chain extenders, and amine chain extenders. Preferably, the multifunctional epoxy oligomer chain extender is one or more selected from ADR-4368 chain extender, ADR-4400 chain extender, and ADR-4370 chain extender, the epoxy polymer chain extender includes one or more selected from SAG-008 chain extender, 6059 chain extender, and 100G chain extender, and the amine chain extender is one or more selected from ethylenediamine, diethylenetriamine, triethylenetetramine, and 3-methylaminopropylamine.
5. The biodegradable 3D printing material according to any one of claims 1 to 4, characterized in that: The nanofiller is one or more selected from carbon nanofillers, metal oxide nanofillers, ceramic nanofillers and polymer nanofillers, preferably one or more selected from hydroxyapatite and calcium carbonate. More preferably, the average particle size of the hydroxyapatite is 50-100nm; the average particle size of the calcium carbonate is 200-500nm.
6. The biodegradable 3D printing material according to any one of claims 1 to 5, characterized in that: The dispersant is one or more selected from ethylenediaminetetraacetic acid, sodium bisulfite, disodium ethylenediaminetetraacetate, and / or The auxiliary agent is one or more selected from plasticizers and antioxidants. Preferably, the plasticizer is one or more selected from epoxidized soybean oil and tributyl citrate, and the antioxidant is one or more selected from antioxidant 1010, antioxidant 1098, and antioxidant 168. Also preferably, the amount of the plasticizer is 1 to 5 parts, and / or the amount of the antioxidant is 0.5 to 5 parts. Preferably, the amount of the antioxidant is 1 to 2 parts.
7. A method for preparing a biodegradable 3D printing material as claimed in any one of claims 1 to 6, comprising the following steps: S1, preparing modified plant fiber powder: placing plant fiber powder and a dispersant in an alkaline solution (for example, sodium hydroxide or potassium hydroxide aqueous solution) for mixing, washing and drying to obtain modified plant fiber powder; S2, dispersing the modified plant fiber powder obtained in S1 in water, adding nanofillers for mixing, so that the nanofillers are combined in the internal pores and the outer surface of the modified plant fiber powder, and drying to obtain a mixed product; S3, putting the mixed product obtained in S2, the biodegradable resin, the chain extender, and the additive into a mixer, and stirring for, for example, 3-5 minutes to obtain a mixture; S4, adding the mixture obtained in S3 into an extruder, and obtaining a biodegradable 3D printing material through melt blending, extrusion, water cooling, air drying, and pulling.
8. The preparation method according to claim 7, wherein: In step S1, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution with a mass fraction of 1%.
9. The preparation method according to claim 7 or 8, wherein: In step S1, the treated plant fiber powder is washed with distilled water until it becomes neutral.
10. The preparation method according to any one of claims 7 to 9, wherein: In step S4, the extruder is a twin-screw extruder, wherein the temperature zones 1 to 6 of the twin-screw extruder are set to 80-110°C, 145-175°C, 160-190°C, 160-190°C, 150-180°C, and 145-175°C respectively; and the main engine speed is 2-30rpm.